Pathogenetic Therapy of Psoriasis by Muramyl Peptide - Guryanova, Svetlana; Udzhukhu, Vladislav; Kubylinsky, Aleksandr (Frontiers in Immunology, 2019)
Psoriasis is a multifactorial disease with a dysregulation in immune system. The aim of this study was to survey the clinical efficacy and safety of muramyl peptide - the ligand of the receptors of innate immunity (drug Licopid®, AO Peptek, Moscow, Russia) in patients with psoriasis. The effect of muramyl peptide on 86 patients with different severity of plaque psoriasis was tested. The Psoriasis Area and Severity Index (PASI), cytokine status and production of nitric oxide in blood serum, and the subsequent course of psoriasis have been evaluated. Evaluation of significance of observed differences was presented by the Student's t-test. As a result of the treatment, clinical cure or improvement was detected in 98.2% of patients (p < 0.05) , while 24.4% had a complete cure. Subsequent observations during four years showed that patients who received muramyl peptide statistically significantly increased relapse-free period. Moreover subsequent relapses of the disease after treatment with muramyl peptide were in much more milder form in the cases of mild psoriasis. The conducted studies showed that monotherapy with muramyl peptide stopped the clinical manifestations of psoriasis, normalized the processes of cytokine-dependent (interleukin (IL) -4, IL-10, IL-12, tumor necrosis factor alpha (TNF-α)) regulation of the immune response and nonspecific resistance, expressed in a decreasing amount of serum antigens sCD54 (soluble intercellular adhesion molecule-1 (sICAM-1)) to reference values (p ≤ 0.01). Taken together, our research demonstrated the effectiveness of therapy with muramyl peptide and moreover, that elevated levels of sCD54 and MIF (p ≤ 0.01) in the serum of patients with psoriasis considered as potential biomarkers of the severity of psoriasis and control over their dynamics have prognostic significance in determining the effectiveness of the therapy.